Transfollicular subcutaneous forehead and brow lift - Anna Karoline Gouveia; Guillermo Loda; Marcela Benez; Anna Beatriz Loda (Surgical & Cosmetic Dermatology, 2025)
The appearance of the upper third of the face is a key indicator of aging and plays a significant role in communication by conveying non-verbal information. Different surgical techniques have been described for the rejuvenation of this region, with transfollicular subcutaneous forehead and brow lift enabling excellent results by lowering the hairline, reducing forehead height, softening forehead and glabellar rhytids, raising the eyebrows, and improving pseudodermatochalasis. This technique offers the advantages of reduced risk of nerve injury and excellent scalp scar camouflage.